Karl Popper and the social sciences - Gorton, William A., 1966- (State University of New York Press, 2006)
"This is the first book-length exploration of Karl Popper's often-neglected contributions to the philosophy of social science. William A. Gorton situates Popper's ideas on social inquiry within the broader framework of his thought, including his philosophy of natural science, his ontological theories, and his political thought. Gorton places special attention on Popper's theory of situational analysis and how it aims to heighten our understanding of the social world by untangling the complex web of human interaction that produces unintended - and often unwanted - social phenomena. Situational analysis, Gorton contends, involves a significant departure from the method of the natural sciences, despite Popper's plea for the unity of scientific method. Gorton also addresses some common misconceptions concerning Popper's stance toward economics and Marxism, making the provocative claim that contemporary analytical Marxism provides the best current example of Popperian social science put into practice."--Jacket
Keywords: Popper, Karl R. -- (Karl Raimund), -- 1902-1994.; Popper, Karl R. -- (Karl Raimund), -- 1902-1994; Social sciences -- Methodology.; Social sciences -- Philosophy.; Political science.; Economics.; Economics; Sciences sociales -- Philosophie.; Économie politique.; economics.; SOCIAL SCIENCE -- Essays.; Political science; Social sciences -- Methodology; Social sciences -- Philosophy